Exploring the genomic mysteries of polyploidy in cotton - Adams, K.L; Wendel, J.F (Biological journal of the Linnean Society, 2004)
For several years allopolyploid cottons have been the subject of evolutionary investigations into the genomic mysteries of polyploidy. An array of genomic interactions have been documented, including interlocus concerted evolution, differential rates of genomic evolution and intergenomic sequence transfer. Substantial alterations in gene expression have occurred in response to allopolyploidization, including gene silencing and expression changes that vary by organ. Some of the molecular phenomena occurring in polyploids appear to be non‐Mendelian. Many of the genomic and expression alterations have occurred on an evolutionary timescale, whereas others reflect more immediate consequences of genomic merger. © 2004 The Linnean Society of London, Biological Journal of the Linnean Society, 2004, 82, 573–581.